Our current equation is:
-8r -31 = -3(5r -6)
To solve for this, we need to get r on one side of the equation and then simplify if needed.
On the right side of the equation, we have a pending Distributive Property, which is when you multiply the number/variable outside of the parenthesis by all numbers/variables in the parenthesis.
Let's simplify this Distributive Property to help understand our equation better.
-3(5r -6)
Multiply -3 by each number/variable separately (unless they are already being multiplied, like 2x, 1/2x, etc).
-3(5r) + -3(-6).
-3(5r) = -15r
-3(-6) = 18 (both negatives need to be in parenthesis to keep a product as negative, and if you do not multiply them in that way, you will end up with a positive product).
Your equation now is:
-8r -31 = -15r + 18
Add 15r to both sides to get r on one side.
7r -31 = 18 is now our current equation.
Add 31 to both sides to get 7r by itself.
7r = 49 is now our equation.
r is still being multiplied by 7, so we need to do the opposite of multiplying by 7.
Divide both sides by 7.
r = 7.
I hope this helps!
The answer is going to be x=22
Step-by-step explanation:
7^3 × 7^(1÷2)
= 7^(3+ 0.5)
=7^3.5 ans
Answer:
-1.2
Step-by-step explanation:
3.8-5=-1.2
lmk if this is right
hope it helped